CURAHAN TAJUK PADA TEGAKAN MODEL ARSITEKTUR POHON AUBREVILLE, LEEUWENBERG DAN STONE DI TIPE PENGGUNAAN LAHAN KEBUN HUTAN SUB DAERAH ALIRAN SUNGAI GUMBASA - Naharuddin, Naharuddin; Bratawinata, Ariffien; Hardwinarto, Sigit; Pitopang, Ramadanil (Universitas Tadulako, 2016)
Throughfall is part of the rainwater that falls onto the surface of the soil through the cracks and the canopy or in the form of runoff from the leaves, twigs or branches. This study aims to determine the effect of rainfall on the stand throughfall Aubreville architecture models, Leeuwenberg and Stone. To calculate the amount of throughfall measurements directly on three models of tree architecture Aubreville, Leeuwenberg and Stone each repeated 3 times measured for 30 times the rainfall event. The results showed the highest throughfall Aubreville models by 18.74% and the smallest model of Stone 12.36% of the total rainfall 413.60 mm. Relations with throughfall precipitation is 75% in model Aubreville, 36% and 43% models Leeuwenberg Stone models.Keywords: Throughfall, stem flow, architecture model, watershed